2002
DOI: 10.1007/bf02344209
|View full text |Cite
|
Sign up to set email alerts
|

Standing-up exerciser based on functional electrical stimulation and body weight relief

Abstract: The goal of the present work was to develop and test an innovative system for the training of paraplegic patients when they are standing up. The system consisted of a computer-controlled stimulator, surface electrodes for quadricep muscle stimulation, two knee angle sensors, a digital proportional-integrative-derivative (PID) controller and a mechanical device to support, partially, the body weight (weight reliever (WR)). A biomechanical model of the combined WR and patient was developed to find an optimum ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…25 This system was designed and developed for quadriceps muscles' re-strength during movements of standing up ± sitting down, induced by FES and supported by a mechanical device for weight relief. The training of muscle conditioning consisted of 3 to 4 sessions/week of 90 min, and lasted 30 sessions.…”
Section: Training Programmentioning
confidence: 99%
“…25 This system was designed and developed for quadriceps muscles' re-strength during movements of standing up ± sitting down, induced by FES and supported by a mechanical device for weight relief. The training of muscle conditioning consisted of 3 to 4 sessions/week of 90 min, and lasted 30 sessions.…”
Section: Training Programmentioning
confidence: 99%
“…The pennation angle of human quadriceps muscle changes monotonically during quadriceps contraction and is a continuously differentiable, positive, monotonic, and bounded function with a bounded first time derivative [21]. The relationship between muscle force and applied voltage is denoted by the unknown function as (6) where is the voltage applied to the quadriceps muscle by electrical stimulation. While exact force versus voltage models are debatable and contain parametric uncertainty, the generally accepted empirical relationship between the applied voltage (or similarly, current, frequency [22], [23], or pulse width) is well established.…”
Section: Muscle Activation and Limb Modelmentioning
confidence: 99%
“…Typically, these approaches have only been empirically investigated and no analytical stability analysis has been developed that provides an indication of the performance, robustness, or stability of these control methods. Some recent studies (e.g., see [6]) also point to evidence that suggests that linear control methods do not yield acceptable performance in practice. The development of a stability analysis for previous PID-based NMES controllers has been evasive because of the fact that the governing equations for a muscle contraction/limb motion are nonlinear with unstructured uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…This system has been mathematically represented by means of a simulation model described in Reference [17]. The model refers to the experimental set-up developed at the Fondazione Don Gnocchi [3,13,18], which is aimed to train the paralysed quadriceps muscles of patients with spinal cord lesion, for the increase of muscle strength and endurance, in view of the functional applications of FES such as walking or cycling.…”
Section: Description Of the Systemmentioning
confidence: 99%
“…On the basis of previous experiences (see Reference [3]), which showed that a non-linear controller is strongly advisable, it was decided to perform a series of preliminary simulation studies, without involving patients; this is to rapidly test an advanced control strategy. Hence, in this work, the correct stimulation pattern is decided by a gain scheduling non-linear feedback controller designed to work on a wide range of operating conditions of the system using only knee joint measurements in order to generate the appropriate electrical stimulation.…”
Section: Introductionmentioning
confidence: 99%